Study of Rail Defect in Klang Valley Double Track - BIN ABDUL AZIZ, AHMAD SHAHIDEN; Joewono Prasetijo ,; Shaiful Amir Leman, (Progress in Engineering Application and Technology, 2023)
Significant challenges to the safety and efficacy of railway systems are posed by rail defects because there is a lack of specific analysis and comprehension of the root causes and trends of these rail defects. This study seeks to identify different types of rail defects, the total number of rail defect, rail defect trend and root causes of rail defect in the KVDT rail network. This study uses the data of rail flaw detection car (RFDC) in 2018,2019 and 2020 to analyze data of rail defects. Rail defect trend and root cause analyses are also performed to determine the underlying causes that have contributed to the occurrence of these defects. This research has identified and analyzed seven types of rail defects in KVDT, namely engine burn fracture, transverse defect, defective weld head, vertical split head, horizontal split web, vertical split web, and bolt hole crack. A research study conducted on seven types of rail defects in KVDT found that defective weld head was the most common defect, followed by engine burn fractures and transverse defects. The trend analysis of rail defects showed that defective weld head and engine burn fractures have been increasing in recent years, while transverse defects have been decreasing. This suggests that the most significant rail defects are changing over time, and that continuous monitoring and mitigation measures are needed to address the most pressing issues. This research highlighted the importance of addressing rail defects in order to ensure safety and operational efficiency. By taking steps to mitigate the most common and significant rail defects, the KTMB can improve the safety of its rail network.